Tackling bullying and harassment at work.- a guide for union reps and workers - Oates, Andrea (London, 2019)
"Bullying and harassment is a daily reality for many workers, making their working lives intolerable. The issue is a major concern for unions, ranking second only to stress as the hazard most likely to be reported by union safety reps. However, unions and workers do not have to simply accept this. Employers have a legal duty to tackle bullying and harassment and there is action that can be taken to deal with the problem. This updated guide provides union reps with examples of best practice and practical guidance on what they can do to prevent bullying and harassment in the workplace, how it can be tackled collectively, and how best to provide support and representation for members who are being bullied and/or harassed at work"